Enantioselective Rh-catalyzed Carboacylation of C=N Bonds via C–C Activation of Benzocyclobutenones - Deng, Lin (J Am Chem Soc, 2015)
Herein we describe the first enantioselective Rh-catalyzed carboacylation of oximes (imines) via C–C activation. In this transformation, the benzocyclobutenone C1–C2 bond is selectively activated by a low valent rhodium catalyst and subsequently the resulting two Rh–C bonds add across a C=N bond, which provides a unique approach to access chiral lactams. A range of polycyclic nitrogen-containing scaffolds were obtained in good yields with excellent enantioselectivity. Further derivatization of the lactam products led to a rapid entry to various novel fused heterocycles.